How educational staff in European schools reform school food systems through 'everyday practices'. Issue 4 (3rd April 2022) - Jones, Mat; Ruge, Dorte; Jones, Verity
Abstract: Schools are recognized as important locales for education and action to change food-related environmental and health behaviours. Research shows the potential for a whole school systems approach to integrate educational activities, food in school, and wider food-related interactions. However, little attention has been given to how theory is put into practice in terms of reforming school food practices in the everyday routines and commitments of schooling. This study aimed to identify how school practitioners operationalise whole systems approaches. The context was an exchange programme involving schools and national school food non-governmental organisations in England, Denmark, and the Czech Republic. Using case study design, the research involved school practitioner interviews and critical group reflection. Participants adopted perspectives and identified actions to create solutions in real-world practice settings, such as themes around, 'persistence, passion and belief'; 'bending the rules' 'supportive, respectful, and united teams'; 'having a holistic vision', 'resistance', and 'making-do'. Drawing upon a conceptual framework concerned with taking an integrated approach, we suggest that these 'everyday practices' have a critical role in food systems reform in schools.